A afetividade no ensino-aprendizagem da matemática financeira - Costa, Mariana Gonçalves (2021)
In accordance with the cultural-historical approach theories, the cognitive and affective dimensions coexist during the student’s development and learning process. During the teacher’s pedagogical practice, the interpersonal relationships that occur in the school space are markedly affective, as well as the decisions taken by him. The objective of this work is to show how affectivity is present during the teaching-learning of Financial Mathematics, seeking to contribute to the educational practice. For this, we seek to understand how human development and learning occur, from the perspective of the psychogenetic theories of Jean Piaget, Lev Vygotsky and Henry Wallon; how affectivity is present in the teaching-learning relationship, in view of the studies, mainly, by Sérgio Antônio da Silva Leite; as the affective dimension involved in the teaching-learning process of Mathematics, based on the studies of Emotional Mathematics by Inês Maria Gómez Chacón. We exemplify the practice of these theories in an activity on compound interest, aimed at high school students.